Progress in additive manufacturing on new materials: A review. Issue 2 (February 2019) - Li, Neng; Huang, Shuai; Zhang, Guodong; Qin, Renyao; Liu, Wei; Xiong, Huaping; Shi, Gongqi; Blackburn, Jon
Abstract: Recent efforts and advances in additive manufacturing (AM) on different types of new materials are presented and reviewed. Special attention is paid to the material design of cladding layers, the choice of feedstock materials, the metallurgical behavior and synthesis principle during the AM process, and the resulted microstructures and properties, as well as the relationship between these factors. Thereafter, the trend of development in the future is forecasted, including: Effects of the particles size and size distribution of powders; Approaches for producing fine microstructures; Opportunities for creating new materials by AM; Wide applications in reconditioning of damaged components; Challenges for deep understanding and applications of the AMed new materials. The idea of "Develop Materials" or "Create Materials" by AM is highlighted, but a series of scientific, technological and engineering problems remain to be solved in future.